Proyecto Unión (2021)
This is a log of the learnings, reflections and results of the work carried out in the Advanced Architecture Unit-Course, where the construction of a high-rise residential building with shops on the first floor is proposed. Intervention area located in present Panamericano School, Calle 26 between Carrera 27 and 27a, in Bogotá, Colombia. The results present an opportunity to improve urban quality in the area, the reactivation of public space and the use of real estate development for projects of public interest.